Response Patterns of Three Types of Biocrust to Reduced Rainfall - Hongyu Jiang; Qianhai Ye; Siqing Wang; Liping Yang; Yali Ma; Yuhan Qi; Haoran Luo; Zhixin Zhou; Qinqin Chang; Li Ma; Hao Wang; Changming Zhao; et al. (Ecosystem Health and Sustainability)
Biological soil crusts (biocrusts), compound organisms covering the terrestrial land surface and consisting of living organisms—algae, lichen, moss, and soil particles—cover ~30% of global drylands and play crucial roles in ecosystem functions and services. Climate change, especially rainfall regime, has been significantly reshaping biocrust dynamic. Notably, 3 biocrust types exhibit distinct properties and show different responses to reduced rainfall. Therefore, it is critical to clarify the dynamics of 3 biocrust types under reduced rainfall. To that end, we conducted a 4-year experiment whose large plot size implicitly involved the impacts of vascular plants on biocrusts, and 24 replicates for each rainfall reduction treatment greatly improved statistical power, to quantify the impact of various levels of rainfall reduction on 3 biocrust types. We used cover percentage of biocrusts as our response variable. Results showed that algae biocrust cover exhibited a limited, still significant, response to rainfall reduction, while lichen biocrust cover demonstrated a more sensitive responses to rainfall reduction and time. As the intensity of rainfall reduction increased, the moss biocrust cover decreased by 47%, 60%, 70%, and 87% across 4 rainfall reduction treatments over 4 years. Specifically, moss biocrust cover showed a delayed response to rainfall reduction, which tended to manifest after the third year. In addition to annual rainfall, rainfall frequency significantly affected all 3 biocrust types. Soil water content might mediate the impacts of the rainfall regime on moss biocrust cover but not on algae and lichen biocrust cover. This study offers a comprehensive evaluation of the overall response of 3 biocrust types to reduced rainfall, thereby enhancing our abilities to mitigate climate change in dryland ecosystems.